Uganda Economic Update, February 2015 : The Growth Challenge--Can Ugandan Cities Get to Work? - World Bank (Washington, DC, 2015)
This Fifth Edition of the Uganda Economic Update presents evidence that if the urbanization process is well managed, it has the potential to stimulate economic growth and to provide productive jobs for a greater proportion of Uganda s young and rapidly expanding population. In many countries across the world, the growth of cities has stimulated the establishment and expansion of productive businesses by reducing the distance between suppliers and customers. The growth of cities has also facilitated provision of social services and infrastructure through economies of scale. These positive effects from urbanization are already visible in Uganda since the poverty rate is seven percentage points lower in urban areas than in rural areas. Most of the recent job creation is found in cities, and social indicators are also better in urban areas, especially in education and health. This report conveys the following key messages: (1) over the past 12 years, the number of people living in Uganda s urban areas has been increasing by an average of 300,000 people per year, (2) during the past few decades, similarly rapid rates of urbanization have been recorded in many emerging countries, (3) as is the case in many other developing countries, the prospects of good jobs, higher incomes and better living conditions in the cities continue to attract Ugandans from rural areas, (4) currently, the opportunity presents itself for Uganda to leverage urbanization to benefit a large proportion of the population, and (5) through the implementation of smart policies, Uganda can ensure that its cities are both competitive and livable.